TELAAH AL ‘URF TERHADAP SISTEM UPAH PENGAIRAN DI DESA GAYAM LOR BOTOLINGGO BONDOWOSO - Ali, Mufti Faqih; Yasid, Abu; Ghozali, Muhammad Lathoif; Latifah, Sofiyatul (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
Al-‘urf, as one of the sources of Islamic law, plays a strategic role in shaping Islamic economic law, particularly in addressing contemporary socio-economic dynamics. This study examines the application of al-‘urf in the wage system for irrigation services in Gayam Lor Village, Botolinggo District, Bondowoso Regency, where no fixed wage standard is predetermined. The compensation mechanism between irrigation workers (lobenyu) and farmers is based on widely recognized local customary practices. This research employs a qualitative method with normative and descriptive-analytical approaches. The findings indicate that the practice constitutes an ijarah (service-based contract) characterized as ujrah al-mithl, since the wage amount is determined flexibly based on field conditions and is not stated during the contract session. Therefore, this ‘urf al-amali practice possesses Sharia legitimacy as long as mutual consent and fairness between both parties are ensured.